2018
DOI: 10.1093/mnrasl/sly141
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a cyclotron line in SXP 15.3 during its 2017 outburst

Abstract: We report the results of AstroSat and NuSTAR observations of the Be/X-ray binary pulsar SXP 15.3 in the Small Magellanic Cloud during its outburst in late 2017, when the source reached a luminosity level of ∼10 38 erg s −1 , close to the Eddington limit. The unprecedented broadband coverage of the source allowed us to perform timing and spectral analysis between 3 and 80 keV. The pulse profile exhibits a significant energy dependence, and morphs from a double peaked profile to a single broad pulse at energies … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…s −1 ). A cyclotron feature was detected at 5 keV from AstroSAT and NuSTAR observations during this outburst with an estimated surface magnetic field of 6 × 10 11 G for the neutron star (Maitra et al 2018). A series of three outbursts followed, with a recurring timescale of ∼ 150 days at peak flux levels of ∼ 4×10 −11 erg.…”
Section: X-ray Variabilitymentioning
confidence: 87%
“…s −1 ). A cyclotron feature was detected at 5 keV from AstroSAT and NuSTAR observations during this outburst with an estimated surface magnetic field of 6 × 10 11 G for the neutron star (Maitra et al 2018). A series of three outbursts followed, with a recurring timescale of ∼ 150 days at peak flux levels of ∼ 4×10 −11 erg.…”
Section: X-ray Variabilitymentioning
confidence: 87%
“…Events were re-binned for plotting purposes only. cretion column (e.g., Tsygankov et al 2017;Maitra et al 2018). In many cases BeXRB spectra show residuals at soft energies.…”
Section: Spectral Propertiesmentioning
confidence: 99%
“…In November 2017 Ducci et al (2017) observed the source in outburst. Maitra et al (2018) observed the source in late 2017 with both NuSTAR and Swift-XRT simultaneously and measured a 3-80 keV luminosity of ∼ 10 38 erg s −1 . We obtained three NuSTAR observations of this source in March, July, and August 2017, respectively (see Table 3).…”
Section: Source 1705 -Detection Of Two Be-xrbsmentioning
confidence: 99%